Deletion of Rap1 protects against myocardial ischemia/reperfusion injury through suppressing cell apoptosis via activation of STAT3 signaling. Issue 3 (5th February 2020) - Cai, Yin; Ying, Fan; Liu, Hao; Ge, Liang; Song, Erfei; Wang, Lin; Zhang, Dengwen; Hoi Ching Tang, Eva; Xia, Zhengyuan; Irwin, Michael G.
Abstract: Ischemic heart disease is a leading cause of morbidity and mortality. Repressor activator protein 1 (Rap1), an established telomere‐associated protein, is a novel modulator of hypoxia‐induced apoptosis. This study aimed to explore the potential direct role of Rap1 in myocardial ischemia/reperfusion injury (I/RI) and to determine the underlying molecular mechanism. In a mouse model of myocardial I/RI (30‐min of left descending coronary artery ligation followed by 2‐h reperfusion), Rap1 deficiency significantly reduced myocardial infarct size (IS) and improved cardiac systolic/diastolic function. This was associated with a reduction in apoptosis in the post‐ischemic myocardium. In H9C2 and primary cardiomyocytes, Rap1 knockdown or knockout significantly suppressed hypoxia/reoxygenation (H/R)‐induced cell injury and apoptosis through increasing the phosphorylation/activation of STAT3 at site Ser 727 and translocation of STAT3 to the nucleus. We surmise this since Stattic (selective STAT3 inhibitor) pretreatment canceled the abovementioned protective effect. Furthermore, co‐immunoprecipitation assay revealed a direct interaction between Rap1 and STAT3, but not JAK2, suggesting that the association of Rap1 with STAT3 may contribute to the reduced activity of STAT3 (Ser 727 ) upon H/R stimulation. In conclusion, Rap1 deficiency protects the heart from ischemic damage through STAT3‐dependent reduction of cardiomyocyte apoptosis, which may yield viable target for pharmacological intervention in ischemic heart disease.